Glycine Level in GOT, GPT Enzyme Activity, and Its Relationship to Heart Disease: Kadar Glisin dalam GOT, Aktivitas Enzim GPT, dan Hubungannya dengan Penyakit Jantung - Al-Fahadi, Nabil Hamdallah; Saleh, Saad Ghanem; Al-Ghadhanfari, Ekram Mohammed Taher (Indonesian Journal on Health Science and Medicine, 2025)
This study aims to study the relationship between glycine levels and the activity of glutamate-oxaloacetate transaminase (GOT) and glutamate-pyruvate transaminase (GPT) in different tissues (blood, heart, liver) and explore the impact of this relationship on heart and liver diseases. Data were collected from thirty patients with varying levels of glycine in the blood, and the activity of GOT and GPT enzymes was measured in blood, heart and liver samples, with the effect of glycine on the activity of these enzymes analyzed. The results showed that glycine levels were positively correlated with GOT and GPT enzyme activities in blood, heart, and liver. For example, in blood, the results showed that GOT enzyme activity was 15.29 U/100ml protein at 0.3% glycine level, and increased to 19.0 U/100ml protein at 8.1% glycine level. In heart, GOT enzyme activity was 18.21 U/100ml protein at 0.3% glycine level, and increased to 18.3 U/100ml protein at 4.0% glycine level. In liver, the enzyme activity was initially 14.72 U/100ml protein at 0.3% glycine level, and then increased to 19.0 U/100ml protein at higher glycine levels. The results also showed a significant increase in the total tissue activity with increasing glycine levels. In blood, the total activity increased from 14.1 U at 0% glycine to 31.4 U at 2.0% glycine. In the heart, the total activity increased from 27.0 U to 33.8 U at the same glycine levels, reflecting the effect of glycine in enhancing the enzyme activity in cardiac tissue. These results are an important step towards understanding the effect of glycine in improving enzyme activity and promoting metabolic balance, especially in the context of heart and liver diseases. The study also highlights the therapeutic potential of glycine as a nutritional compound in mitigating the effects of oxidative stress and improving the health of damaged tissues. Based on these results, glycine may play a pivotal role in developing new therapeutic strategies to enhance the health of heart and liver tissues. Finally, this study contributes to adding new knowledge about the role of glycine in improving the levels of enzymes that contribute to the balance of metabolic reactions and protecting tissues from damage resulting from oxidative stress, which opens new horizons for medical and therapeutic research in this field. Highlights: Glycine enhances GOT & GPT enzyme activity in blood, heart, and liver. Increased glycine levels improve metabolic balance and tissue health. Potential therapeutic role of glycine in heart and liver diseases. Keywords: Glycine, Enzyme Activity, Metabolic Balance, Heart Health, Liver Function